(untitled) (Journal of the College of Basic Education, 2019)
Mikhail Lermontov is a prominent figure in Russian literature, because his literary output contained authentic realism and outstanding art. The Russian reader, who inherited Bushkin’s throne, did not recognize the Arab reader, Lermantov is associated with the poets of the Danish movement and is the last representative of the direction of revolutionary romance and has his own place in Russian literature, and through the product from the thirties. And transformed Lermantov from the romantic doctrine to realistic photography of life and appeared in the product of prose and revolves around the focus of the poet influenced the Prophet (r) specifically in the poem (the Prophet). After the presentation of the poem Lermantov, we offer an analysis of the poem of the Arab poet Ahmed Shawki (Amir poets) and compare the poem Lermantov and access to the thought and axis, which will be clear and visible and derived from the life and thought of the Prophet Muhammad peace be upon him and give to the nations, To the literary, creative and aesthetic purpose of both poems, which derived a great human subject, namely, the character of the Prophet Muhammad, may God bless him and grant him peace, and what characterized this individual personality in carrying the burdens and tragedies in order to reach the sacred goal of reform and equality among human beings.